Effect of Omega-3 Supplementation in Patients With Smell Dysfunction Following Endoscopic Sellar and Parasellar Tumor Resection: A Multicenter Prospective Randomized Controlled Trial. Issue 2 (17th January 2020) - Yan, Carol H; Rathor, Aakanksha; Krook, Kaelyn; Ma, Yifei; Rotella, Melissa R; Dodd, Robert L; Hwang, Peter H; Nayak, Jayakar V; Oyesiku, Nelson M; DelGaudio, John M; Levy, Joshua M; Wise, Justin; et al.
Abstract: BACKGROUND: Endoscopic endonasal approaches pose the potential risk of olfactory loss. Loss of olfaction and potentially taste can be permanent and greatly affect patients' quality of life. Treatments for olfactory loss have had limited success. Omega-3 supplementation may be a therapeutic option with its effect on wound healing and nerve regeneration. OBJECTIVE: To evaluate the impact on olfaction in patients treated with omega-3 supplementation following endoscopic skull base tumor resection. METHODS: In this multi-institutional, prospective, randomized controlled trial, 110 patients with sellar or parasellar tumors undergoing endoscopic resection were randomized to nasal saline irrigations or nasal saline irrigations plus omega-3 supplementation. The University of Pennsylvania Smell Identification Test (UPSIT) was administered preoperatively and at 6 wk, 3 mo, and 6 mo postoperatively. RESULTS: Eighty-seven patients completed all 6 mo of follow-up (41 control arm, 46 omega-3 arm). At 6 wk postoperatively, 25% of patients in both groups experienced a clinically significant loss in olfaction. At 3 and 6 mo, patients receiving omega-3 demonstrated significantly less persistent olfactory loss compared to patients without supplementation ( P  = .02 and P  = .01, respectively). After controlling for multiple confounding variables, omega-3 supplementation was found to be protective against olfactory loss (odds ratio [OR] 0.05, 95% CI 0.003-0.81, P  = .03). Tumor functionality was a significant independent predictor for olfactory loss (OR 32.7, 95% CI 1.15-929.5, P  = .04). CONCLUSION: Omega-3 supplementation appears to be protective for the olfactory system during the healing period in patients who undergo endoscopic resection of sellar and parasellar masses.